2002
DOI: 10.1039/b206996b
|View full text |Cite
|
Sign up to set email alerts
|

Formation of crystalline nanosized titania in reverse micelles at room temperature

Abstract: Shuttle-like crystalline TiO 2 nanoparticles were synthesized by hydrolysis of titanium tetrabutoxide in the presence of acids in NP-5 (Igepal CO-520)-cyclohexane reverse micelle at room temperature. Pure rutile nanoparticles were obtained at appropriate acid concentrations. The influences of various reaction conditions, such as concentration and type of acid, water content, H 2 O/Ti molar ratio, and reaction time, on the formation, crystal phase, morphology, and size of the TiO 2 particles were investigated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
76
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 126 publications
(89 citation statements)
references
References 24 publications
(27 reference statements)
5
76
0
4
Order By: Relevance
“…The method is based on oxidizing of Ni 2+ to NiO2 (nickel peroxide) and then converting this peroxide to NiO by treating it with ethanol in the presence of a surfactant. The use of surfactant is in fact somehow similar to the reverse -micellar method which has been recently demonstrated as a versatile route to produce a variety of nanoparticles [27,28,29,30] . The effect of different surfactants on the size of the as-prepared nanosized NiO is also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…The method is based on oxidizing of Ni 2+ to NiO2 (nickel peroxide) and then converting this peroxide to NiO by treating it with ethanol in the presence of a surfactant. The use of surfactant is in fact somehow similar to the reverse -micellar method which has been recently demonstrated as a versatile route to produce a variety of nanoparticles [27,28,29,30] . The effect of different surfactants on the size of the as-prepared nanosized NiO is also investigated.…”
Section: Introductionmentioning
confidence: 99%
“…Generally the crystals adopt raphides or styloids shapes. Some studies have focused on developing and understanding interactions between calcium oxalate crystals, organic templates and additives [6,7]. For example, Langmuir monolayer [8][9][10], membrane vesicles [11], and phospholipids micelles [12] have been used for the direct crystallization of calcium oxalate.…”
Section: Introductionmentioning
confidence: 99%
“…TiO2 nanoparticles with diameters varing from 10 to 20 nm were produced by the controlled hydrolysis of titanium tetraisopropoxide (TTIP) in the presence of reverse micelles formed in CO2 with the surfactants ammonium carboxylate perfluoropolyether (PFPECOO −+ NH4) (Mw = 587) and poly(dimethyl amino ethyl methacrylate-block-1H, 1H, 2H, 2H-perfluorooctyl methacrylate) (PDMAEMA-b-PFOMA) [57]. Hernandez et al [58] reported the synthesis of TiO2 nanoparticles with a mean diameter of 3.5 ± 0.7 nm inside sodium bis (2-ethylhexyl) [59]. 0D ZnO nanoparticles have been synthesized in reverse micelles or microemulsions, for instance, polystyrene-b-polyacrylic acid (PS(10912)-b-PAA(3638)) copolymer, PEG NP-5/cyclohexane, AOT, non-ionic Pluronic F127, anionic surfactant sodium dodecyl sulfate (SDS), etc.…”
Section: Surfactant-assisted Synthesis Of 0d Nanostructuresmentioning
confidence: 99%